2023
DOI: 10.1117/1.jbo.28.10.102904
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric imaging for cervical pre-cancer screening aided by machine learning: ex vivo studies

Demelza Robinson,
Kevin Hoong,
Willem Bastiaan Kleijn
et al.

Abstract: .SignificanceWide-field imaging Mueller polarimetry is an optical imaging technique that has great potential to become a reliable, fast, non-contact in vivo imaging modality for the early detection of, e.g., deceases and tissue structural malformations, such as cervical intraepithelial neoplasia, in both clinical and low-resource settings. On the other hand, machine learning methods have established themselves as a superior solution in image classification and regression tasks. We combine Mueller polarimetry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The minimum value of the entropy would be expected when all pixel values for each patch are equal, thus indicating the homogeneity of the measured medium. On the other hand, the maximum value of the entropy for a given image patch would be achieved when the image pixel values are uniformly distributed within the closed interval [0, 2 16 ], indicating the random fluctuations of the medium's properties.…”
Section: Transmission Mueller Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum value of the entropy would be expected when all pixel values for each patch are equal, thus indicating the homogeneity of the measured medium. On the other hand, the maximum value of the entropy for a given image patch would be achieved when the image pixel values are uniformly distributed within the closed interval [0, 2 16 ], indicating the random fluctuations of the medium's properties.…”
Section: Transmission Mueller Microscopymentioning
confidence: 99%
“…In general, light-tissue interactions have been well studied, and using polarized light as a tool for the analysis of the inner structure of biological tissue has found applications in tissue characterization and the detection of both benign and malignant lesions [13][14][15][16][17][18][19][20][21]. Initially, the membrane integrity brake, caused by cryo-injury, is anticipated to be followed by changes in the tissue structure and its morphology [10,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Polarization-based optical modalities are sensitive to the micro-structure of biological tissue and have found its place in pre-clinical and clinical applications [1][2][3][4][5]. It was shown that polarized light can be used for non-invasive diagnosis of benign and malignant lesions [6][7][8][9][10][11][12]. Along with diffuse reflectance, fluorescence, Raman spectroscopy and other optical techniques, tissue polarimetry can be used as label-free modality providing supplementary information for skin diagnosis [10,13].…”
Section: Introductionmentioning
confidence: 99%